2018
DOI: 10.1016/j.jclinepi.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

No difference in knowledge obtained from infographic or plain language summary of a Cochrane systematic review: three randomized controlled trials

Abstract: Although the infographic format was perceived as more enjoyable for reading, it was not better than a traditional, text-based PLS in the translation of knowledge about findings from a Cochrane systematic review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 22 publications
3
94
0
5
Order By: Relevance
“…In three small trials (334 cases overall), Buljan et al (2017) compared a scientific abstract, a plain language summary, and an infographic as ways of presenting knowledge about the results of the Cochrane reviews (Cochrane Database of Systematic Reviews). The audience included doctors (111 intervention, 60 control), university students (46 intervention, 18 control) and lay consumers (45 intervention, 54 control).…”
Section: How To Best Summarise and Present Robust Evidencementioning
confidence: 99%
“…In three small trials (334 cases overall), Buljan et al (2017) compared a scientific abstract, a plain language summary, and an infographic as ways of presenting knowledge about the results of the Cochrane reviews (Cochrane Database of Systematic Reviews). The audience included doctors (111 intervention, 60 control), university students (46 intervention, 18 control) and lay consumers (45 intervention, 54 control).…”
Section: How To Best Summarise and Present Robust Evidencementioning
confidence: 99%
“…evidence about test accuracy) [7]. Regarding actual information extraction, one study found that university students more easily extract information from PLS compared to scientific abstracts of Cochrane systematic reviews, also reporting a better reading experience and higher user-friendliness [8]. Yet, a different study on university students' information extraction from Cochrane systematic reviews found neither a statistically significant difference between PLS and scientific abstracts for Cochrane systematic reviews with clear findings, nor for Cochrane systematic reviews with unclear findings [9].…”
Section: Plos Onementioning
confidence: 99%
“…To date, research on PLS has largely focused on the biomedical literature [6][7][8][9]. However, psychology also constitutes a relevant field for decision-making processes, in which misconceptions are widespread [10,11] and resistant to revision [12].…”
Section: Introductionmentioning
confidence: 99%
“…The packaging waste problem can only be resolved if manufacturers, designers, and users actively play a role in protecting the environment in conjunction with government regulations and policies. Buljana et al [38] found that infographics gave people better reading experience; to this end, our goal in this study was to examine how infographics could be used to nurture pro-environmental attitudes, using postal packaging as the vehicle. While there are a number of definitions of infographic design in the domestic and international literature, the infographics dimensions of our questionnaire were based on factors identified by committee members of the Society for News Design (SND) in 2009 [39], which are: (1) attractiveness, (2) clarity, (3) simplicity, (4) flow, and (5) wordlessness.…”
Section: Literature On Infographicsmentioning
confidence: 99%